Online Single Submission Institution Existency in Land Technical Considerations - Susi Andriyani; Ira Alia Maerani (Sultan Agung Notary Law Review, 2020)
The enactment of Government Regulation Number 24 of 2018 which introduces the existence of an Online Single Submission (OSS) institution has brought many changes in various fields, one of which is in the field of land services. This study analyzes the implementation of land technical considerations through the OSS institution and the constraints in implementing land technical considerations through the OSS institution. The research method used is normative legal research with a statutory approach and a conceptual approach. The results show that the implementation of land technical considerations through the OSS institution is aimed at providing convenience in processing permits in order to improve the investment climate in Indonesia.